Can Habitat Management Mitigate Disease Impacts on Threatened Amphibians?. Issue 2 (29th May 2017) - Heard, Geoffrey W.; Scroggie, Michael P.; Ramsey, David S. L.; Clemann, Nick; Hodgson, Jenny A.; Thomas, Chris D.
Abstract: Chytridiomycosis has decimated amphibian biodiversity. Management options for the disease are currently limited, but habitat manipulation holds promise due to the thermal and physicochemical sensitivities of chytrid fungi. Here, we quantify the extent to which habitat management could reduce metapopulation extinction risk for an Australian frog susceptible to chytridiomycosis. Our modeling revealed that: (1) habitat management is most effective in climates where hosts are already less susceptible to the disease; (2) creating habitat, particularly habitat with refugial properties adverse to the pathogen, may be substantially more effective than manipulating existing habitat; and (3) increasing metapopulation size and connectivity through strategic habitat creation can greatly reduce extinction risk. Controlling chytridiomycosis is a top priority for conserving amphibians. Our study provides impetus for experiments across a range of species and environments to test the capacity of habitat management to mitigate the impacts of this pervasive disease.